2015
DOI: 10.1371/journal.pone.0129421
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Diabetes Monocyte MicroRNA and mRNA Expression: Dyslipidemia Associates with Increased Differentiation-Related Genes but Not Inflammatory Activation

Abstract: There is increasing evidence that inflammatory macrophages in adipose tissue are involved in insulin resistance of type 2 diabetes (T2D). Due to a relative paucity of data on circulating monocytes in T2D, it is unclear whether the inflammatory changes of adipose tissue macrophages are reflected in these easily accessible cells.ObjectiveTo study the expression pattern of microRNAs and mRNAs related to inflammation in T2D monocytes.DesignA microRNA finding study on monocytes of T2D patients and controls using ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…We previously found a similar gene expression profile, i.e., a reduced pro-inflammatory cluster 1 and raised HGF expression, in the circulating monocytes of 64 T2D patients (23, 36). These T2D patients were on average 62 years old.…”
Section: Discussionmentioning
confidence: 59%
“…We previously found a similar gene expression profile, i.e., a reduced pro-inflammatory cluster 1 and raised HGF expression, in the circulating monocytes of 64 T2D patients (23, 36). These T2D patients were on average 62 years old.…”
Section: Discussionmentioning
confidence: 59%
“…The main characteristics extracted from various datasets are summarized in Table 1, which includes the number of patients investigated, the measurement platform, type of sample used and the identity of miRNAs in the study [23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81]. Comparing results from multiple tissues provides an overall view of the impact of miRNAs in T2DM pathology.…”
Section: Resultsmentioning
confidence: 99%
“…22 It is also found that mRNA and miRNA expression from monocytes is altered, resulting in the upregulation of TNF-α and IL-6 gene expression 23 and downregulation of miR-146a and miR-155 expression, the key regulators of inflammatory process. [24][25][26] IL-10 is an anti-inflammatory cytokine secreted by Treg cells, Th2 cells, B cells, macrophages, and DCs. 27 IL-10 Figure 2 Scatter plots of PHA-induced TNF-α/IFN-γ ratio against the baseline IL-10 level for control subjects ( ) and patients with T2DM ( ).…”
Section: Discussionmentioning
confidence: 99%